INTELIGENCIA DE NEGOCIOS AL PROCESO DE LA EVALUACION DOCENTE (2016)
Universities require for their development integrating databases to support decision making in this way the teacher evaluation improved the relationship with the students, allowing them to be more competitive, improving internal processes, minimizing costs and increasing profits, this is how the holy Tomas University branch Tunja has used the draft business Intelligence process for Teacher evaluation, which allows its executives to use the data Warehouse and OLAP technology in the analysis of information generated by the databases, once implemented concluded to do academic track individual teachers, schools and the university in general detailing its behavior for each of your Items and features.Data mining algorithms is seeking “knowledge” of different data bases with history teachers during their University course. The purpose of knowledge is preventing the Executives on irregular situations, anomalies and even negative events not detected early.